Use of Digital Tools for Sales Management in The Retail Business. - Narek Halstian (Emerging Frontiers Library for The American Journal of Management and Economics Innovations, 2025)
This article substantiates the necessity of transitioning to an integrated digital sales ecosystem as a key factor of competitiveness. The relevance of the study is determined by the rapid growth of electronic commerce and the approach of the online channel share to 20% in global retail, which renders traditional methods of sales management economically inefficient. The author emphasizes that digital transformation should be regarded not as a one-off project but as a continuously accelerating positive feedback loop requiring end-to-end integration of CRM, POS, BI, and ERP/OMS. The objective of the study is to systematize and analyze contemporary digital solutions applied to sales management in the retail business, as well as to identify the mechanisms of their interaction and their impact on key operational indicators. The methodological basis comprised a comparative analysis of reports by UNCTAD, Emarketer, McKinsey, Intellias, and leading industry research, as well as content analysis of practical case studies and statistical data. The theoretical part examines the four layers of the sales tech stack, while the empirical part provides examples of the implementation of AI modules, predictive analytics, and omnichannel platforms. The novelty of the research lies in the comprehensive consideration of the chain CRM → POS → BI → ERP/OMS as a single data loop that enables enterprises to achieve operational transparency of sales, responsiveness to demand, and process scalability. Additionally, current trends in marketing automation, SFA applications, and AR/VR solutions are analyzed, as well as the organizational and behavioral factors influencing the success of digital initiatives. Key findings: integration of digital tools ensures up to 65% reduction in revenue loss through AI demand forecasting and a 5–15% increase in revenues; omnichannel transforms the customer journey, increasing the average basket value and customer retention; the implementation stages (audit – pilot – phased migration) are critical for minimizing risks; the main barriers remain data fragmentation, employee resistance, cyber threats and the risk of vendor lock-in, overcoming which requires a systemic approach to training, security and data management. This article will be useful for executives of retail companies, IT directors, digital transformation consultants, and researchers in the field of retail.